Persepsi Klien tentang Bauran Pemasaran terhadap Keputusan Pemilihan Layanan Poliklinik - Riska Yanuarti; Fitri Wulandari; Eva Oktavidiati; Bintang Agustina Pratiwi; Oktarianita Oktarianita (STIKes Surya Global Yogyakarta, 2022)
Background of Study: Th increasing number of hospitals has made the people to free choose services that match their expectations. The number of patient visits at the Outpatient Polyclinic of Bhayangkara Hospital Level III Pattern Bengkulu has decreased from 2016 to 2019. The decision to visit the community is influenced by how they perceive the stimuli they receive in the marketing mix consisting of Product, Price, Promotion and Place. This study aims to determine the relationship between client perceptions of the marketing mix with the decision to choose polyclinic services at Bhayangkara Hospital Level III, Bengkulu City Police.Methods: The research design was cross-sectional. The number of samples were 92 clients who used outpatient poly services taken by accidental sampling technique. The research was held from July to August 2019. The data analysis technique used Chi Square.Results: The results showed that 55.4% of respondents had a good perception of the hospital's marketing mix and 62% of respondents made the decision to re-elect outpatient polyclinic services. Bivariate analysis showed p value = 0.001 which means that there was a relationship between the client’s perception of the marketing mix on the decision to choose an outpatient polyclinic service at Bhayangkara Hospital Level III Bengkulu Police.Conclusion: There is relationship between the client’s perception of the marketing mix on the decision to choose an outpatient hospital polyclinic.Keywords : Marketing Mix, Decision, Election, Polyclinic